Cannabinoid Concentrations Detected in Fatal Road Traffic Collision Victims Compared with a Population of Other Postmortem Cases. (6th January 2020) - Andrews, Rebecca; Murphy, Kevin G; Nahar, Limon; Paterson, Sue
Abstract: BACKGROUND: Acute cannabis consumption nearly doubles the risk of motor vehicle collision resulting in injury or death. Limited data have been published regarding the concentrations of cannabinoids associated with fatal road traffic collisions (RTCs), and these have not previously been compared to a population of other postmortem cases. METHODS: We conducted analysis for cannabinoids [Δ 9 -tetrahydrocannabinol (THC), 11-hydroxy-THC, 11-nor-THC-9-carboxylic acid, cannabidiol, and cannabinol], drugs, and alcohol on consecutive fatal RTC cases (100) and non-RTC cases (114) from coroners' jurisdictions in London and southeast England and compared the data. RESULTS: The incidence of cannabinoids detected in non-RTC and RTC cases was similar (25% vs 21%, P = 0.44), but THC was detected more frequently (90% vs 59%, P = 0.01) and at significantly higher concentrations in the cannabinoid-positive RTC cases than the non-RTC cases ( P = 0.01). The distribution of non-RTC and RTC cases over 4 categories of THC concentration was significantly different ( P = 0.004). There was no significant difference in the concentrations of other cannabinoids detected between the 2 groups. Cannabinoids were detected in more fatal RTC cases (21 ) than alcohol >80 mg/dL (17 ). Detection of other drugs was low compared to cannabis and alcohol. CONCLUSIONS: These first data on the concentrations of cannabinoids in the postmortem blood of fatal RTC victims compared with a population of other routine coroners' cases highlight the importance of specifically measuring THC concentrations in the blood to aid interpretation of postmortem cases where cannabis may be implicated.